Understanding planning process in shariah audit: the case of takaful operator in Malaysia - Mohamad Puad, Noor Aimi; Shafii, Zurina; Abdullah, Nurdianawati Irwani (Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan, 2018)
The function of audit from the Islamic view is much more important as it manifests the accountability of the auditors not only to the stakeholders, but ultimately to the Creator, Allah s.w.t as the Muslims believe that one’s action and thoughts are always being watched by Allah (the concept of Muraqabah). based on shari’ah governance framework which was circulated in 2011, the function of shari’ah audit considered as mandatory for every Islamic financial institutions. The non-availability of comprehensive shariah audit framework has become one of the challenges in conducting shariah audit and makes the industry practice differently. The planning stage is very crucial in audit practice as it reflects the whole process of auditing. The aim of the study is to understand the planning process in shariah audit mainly in Takaful industry by using qualitative approach. The study has been carried out through a multiple case study, which compared the practices of three Takaful Operators, gathering evidence by interviews with auditors who performed shariah audit functions .This study highlights diversity in planning process although there are also some similarities between Takaful Operator. This study may provide deeper understanding on planning process and some relevant recommendations for future development of shariah audit practices in Islamic financial institutions particularly for Takaful industry.